2021
DOI: 10.1126/scitranslmed.abc2816
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cytoplasmic membranes synergistically enhance the antitumor activity of autologous cancer vaccines

Abstract: Cancer vaccines based on resected tumors from patients have gained great interest as an individualized cancer treatment strategy. However, eliciting a robust therapeutic effect with personalized vaccines remains a challenge because of the weak immunogenicity of autologous tumor antigens. Utilizing exogenous prokaryotic constituents that act as adjuvants to enhance immunogenicity is a promising strategy to overcome this limitation. However, nonspecific stimulation of the immune system may elicit an undesirable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 51 publications
0
106
0
Order By: Relevance
“…We examined the molecular composition of EMs proteins through SDS-PAGE assay (Figure S5c) and subjected proteins in EMs to proteomic identification by mass spectrometry (Figure S5d). We analyzed the relative abundance of potential adjuvants in the total protein, including flagellin (FliC), outer membrane protein A (OmpA), phosphatidylserine decarboxylase (Psd), and 18 kinds of lipoproteins. These various PAMPs in EMs could guarantee their ability in better immune activation than single component synergistically.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the molecular composition of EMs proteins through SDS-PAGE assay (Figure S5c) and subjected proteins in EMs to proteomic identification by mass spectrometry (Figure S5d). We analyzed the relative abundance of potential adjuvants in the total protein, including flagellin (FliC), outer membrane protein A (OmpA), phosphatidylserine decarboxylase (Psd), and 18 kinds of lipoproteins. These various PAMPs in EMs could guarantee their ability in better immune activation than single component synergistically.…”
Section: Resultsmentioning
confidence: 99%
“…They vaccinated tumor-bearing mice with the nanoparticles and showed improved activation of DCs and Ag-specific T cells. The nanoparticle vaccination enhanced mouse survival and provided a long-term anti-tumor effect [184]. Similar to stimulation by bacteria, tumor inflammation stimulated by a virus enhances the efficacy of DC vaccines.…”
Section: Combination Therapymentioning
confidence: 99%
“…Using HEK293derived TLR reporter cells, [30] we found that OMV-LL significantly activated TLR2, TLR4, and TLR5 and slightly activated TLR9 (Figure 2B,C), which can be activated by lipoproteins, lipopolysaccharide (LPS), flagellin, and microbial genomic DNA, respectively, all of which are expected to be present in bacteria-derived OMVs. [29,31] Next, we evaluated the innate immunity stimulation and antigen presentation induced by our OMV-based mRNA vaccine in BMDCs. We synthesized mRNA encoding an antigenic epitope of ovalbumin (257-SIINFEKL-264, OVA; mRNA OVA ) and used OMV-L (OMV-L-mRNA OVA ) or OMV-LL (OMV-LL-mRNA OVA ) to deliver it.…”
Section: Innate Immunity Activation and Antigen Presentation Mediated...mentioning
confidence: 99%